Autophagy during Proliferation and Encystation in the Protozoan Parasite Entamoeba invadens - Picazarri, Karina (American Society for Microbiology (ASM), 2008)
Autophagy is one of the three systems responsible for the degradation of cytosolic proteins and organelles. Autophagy has been implicated in the stress response to starvation, antigen cross-presentation, the defense against invading bacteria and viruses, differentiation, and development. Saccharomyces cerevisiae Atg8 and its mammalian ortholog, LC3, play an essential role in autophagy. The intestinal protozoan parasite Entamoeba histolytica and a related reptilian species, Entamoeba invadens, possess the Atg8 conjugation system, consisting of Atg8, Atg4, Atg3, and Atg7, but lack the Atg5-to-Atg12 conjugation system. Immunofluorescence imaging revealed that polymorphic Atg8-associated structures emerged in the logarithmic growth phase and decreased in the stationary phase and also increased in the early phase of encystation in E. invadens. Immunoblot analysis showed that the increase in phosphatidylethanolamine-conjugated membrane-associated Atg8 was also accompanied by the emergence of Atg8-associated structures during the proliferation and differentiation mentioned above. Specific inhibitors of class I and III phosphatidylinositol 3-kinases simultaneously inhibited both the growth of trophozoites and autophagy and also both encystation and autophagy in E. invadens. These results suggest that the core machinery for autophagy is conserved and plays an important role during proliferation and differentiation in Entamoeba.